A Bounded Strategy of the Mobile Robot Coverage Path Planning Based on Lorenz Chaotic System. (1st June 2016) - Li, Caihong; Song, Yong; Wang, Fengying; Wang, Zhiqiang; Li, Yibin
According to the requirements of the mobile robot complete coverage path planning for some special missions, this paper introduces a bounded strategy based on the integration of the Lorenz dynamic system and the robot kinematics equation. Chaotic variables of the Lorenz system are confined in a limited range, while when they are used to produce the robot's coordinate position, the trajectory range is determined by the starting point, iterative times, and iterative step. The proposed bounded strategy can constrain all the robot positions in the workplace by a mirror mapping method that can reflect the overflow waypoints returning to it. Moreover, the statistical characteristics of the Lorenz chaotic variables and the robot trajectory are discussed in order to choose the best mapping variable. The simulation results show that the bounded strategy that uses the chosen variable can achieve a higher coverage rate contrary to other similar works.